2001
DOI: 10.1016/s0168-583x(01)00350-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of PIXE analyses using a funny filter

Abstract: Light and heavy trace elements can be analysed simultaneously by particle-induced X-ray emission (PIXE) using an Al-funny filter (a filter with a hole drilled at its centre, placed in front of the detector window). The treatment of spectra, performed using the GUPIX code, requires the determination of an instrumental constant H. In theory and when using ordinary filters, H is a constant corresponding to the detection solid angle. In contrast, we have observed that H varies with X-ray energy using a funny filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The ''funny filter'' [15,16], with a very small central aperture whose area was a few percent of the detector surface area, placed in front of the X-ray detector, allowed both the lighter (13 6 Z 6 22) and heavier elements (Z > 22) to be detected simultaneously instead of using a dual-detector system. However, the drawback of this kind of absorber was that it made the instrumental constant H, a constant equal to the detector solid angle theoretically, vary dramatically with X-ray energies.…”
Section: Methodsmentioning
confidence: 99%
“…The ''funny filter'' [15,16], with a very small central aperture whose area was a few percent of the detector surface area, placed in front of the X-ray detector, allowed both the lighter (13 6 Z 6 22) and heavier elements (Z > 22) to be detected simultaneously instead of using a dual-detector system. However, the drawback of this kind of absorber was that it made the instrumental constant H, a constant equal to the detector solid angle theoretically, vary dramatically with X-ray energies.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the errors from the parameters of the X-ray detector, atomic parameters used in the GUPIXWIN code, the parameters of the funny filter, etc., the H-value is no longer a constant proportional to the solid angle of the X-ray detector, as in an ideal condition. Instead, the H-value changes with the characteristic X-ray energies of sample elements bombarded by incident protons [12]. In this experiment, 10 single-element thick targets (i.e., Al, Si, Ti, Fe, Ni, Zn, Ge, Zr, Mo and Ag) with a purity of 99.99% were used to measure the H-values under the same experimental conditions.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A pinhole filter is made by drilling a hole at the center of an absorber. The pinhole creates a passage for the low energy Xrays with a reduced solid angle [13]. In this work one kapton absorber, two mylar absorbers have been used along with two pinhole absorbers.…”
Section: The Absorbers Used In the Experimentsmentioning
confidence: 99%
“…In this case, we found that the correction factors for most elements of our standard samples were not unity. Then we adjusted the thickness of the absorber in GUPIX input so that the correction factor for most of the elements tended towards unity [13,15]. After several iterations we were satisfied with the correction factors and we recorded the effective thickness of that absorber.…”
Section: Description Of the Measurementsmentioning
confidence: 99%